IMPLEMENTASI TEKNIK SEO (SEARCH ENGINE OPTIMIZATION) UNTUK OPTIMASI WEBSITE PENJUALAN DI LESTARI JAYA MEBEL - Isbandi Isbandi; Zatnika Zatnika; Edwin Triyatna (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
The background of this research is to help Micro, Small and Medium Enterprises (MSMEs) which need promotional media in the form of websites. Therefore the author has an idea to implement SEO (Search Engine Optimization). SEO (Search Engine Optimization) is a technique for improving a website in the search results of search engines such as Google, Bing, etc. SEO (Search Engine Optimization) is an important marketing strategy for increasing the visibility of a website and the number of organic visitors to the intended site. This research uses quantitative methods. Data collected by online survey and interview techniques. Toko Lestari Jaya Mebel has not been ranked optimally enough on search engines or search engines, with the implementation of SEO (Search Engine Optimization) techniques it is hoped that it can improve the website's position on search engines. So that the site can be easily found and compete with competitors, and is expected to increase sales.